AUTS2 Regulates RNA Metabolism and Dentate Gyrus Development in Mice. (19th May 2021) - Castanza, Anthony S; Ramirez, Sanja; Tripathi, Prem P; Daza, Ray A M; Kalume, Franck K; Ramirez, Jan-Marino; Hevner, Robert F
Abstract: Human AUTS2 mutations are linked to a syndrome of intellectual disability, autistic features, epilepsy, and other neurological and somatic disorders. Although it is known that this unique gene is highly expressed in developing cerebral cortex, the molecular and developmental functions of AUTS2 protein remain unclear. Using proteomics methods to identify AUTS2 binding partners in neonatal mouse cerebral cortex, we found that AUTS2 associates with multiple proteins that regulate RNA transcription, splicing, localization, and stability. Furthermore, AUTS2-containing protein complexes isolated from cortical tissue bound specific RNA transcripts in RNA immunoprecipitation and sequencing assays. Deletion of all major functional isoforms of AUTS2 (full-length and C-terminal) by conditional excision of exon 15 caused breathing abnormalities and neonatal lethality when Auts2 was inactivated throughout the developing brain. Mice with limited inactivation of Auts2 in cerebral cortex survived but displayed abnormalities of cerebral cortex structure and function, including dentate gyrus hypoplasia with agenesis of hilar mossy neurons, and abnormal spiking activity on EEG. Also, RNA transcripts that normally associate with AUTS2 were dysregulated in mutant mice. Together, these findings indicate that AUTS2 regulates RNA metabolism and is essential for development of cerebral cortex, as well as subcortical breathing centers.